The moderating effects of outside directors on the relationship between managerial overconfidence and earnings management: evidence from Korea - Seo, Min Geun; Yoon, Sung Yong (Journal of Business Economics and Management, 2025)
The subjective judgment and discretionary actions of a manager can influence the core strategy, investment, operations, and decision-making of a company. Managerial actions from the top, particularly the board, plays a vital role in addressing this inclination. While scholars have shown interest in examining managers’ overconfidence tendencies in recent years, few have explored the characteristics of the board members. According to the study, a high proportion of outside directors on the board of Korean companies has been observed to alleviate upward earnings management driven by managerial overconfidence. The obtained results emphasize the significance of the board of directors in enterprises and contribute to theories related to managerial characteristics. This study aims to bridge the research gap concerning managers’ tendencies of overconfidence while expanding the existing knowledge in this field. Firstly, this study aims to address the need to identify cognitive characteristics of managers. Secondly, it investigates the impact of the board of directors’ characteristics on managers’ tendencies towards overconfidence.